TO EVALUATE THE MORPHOLOGICAL AND MORPHOMETRIC FEATURES OF ADULT HUMAN CADAVERIC RIGHT LUNG IN NORTH INDIAN POPULATION - KAUR, KULBIR; SINGLA, RAJAN KUMAR; SIDHU, VANDANA; SHARMA, RAVI KANT (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: In the present study, different morphological and morphometric features of adult human cadaveric right lungs were observed and noted on the predesigned pro forma. Not much of such measurements have been done in the past. The mean values and standard deviations are calculated. The data thus obtained were tabulated scrutinized, analyzed, and compared with the earlier studies wherever possible. If any variant from the normal is observed, an attempt has been made to explain the same on ontogenic or phylogenic basis. Methods: The present study has been conducted on 50 adult human cadaveric right lungs obtained from embalmed cadavers, used for dissection in the department of Anatomy, Govt. Medical College, Amritsar, formed the material for the current study. Results: Majority of the lungs (49 [98%]) were spongy in texture while 1 (2%) lung was firm to touch. It is evident that majority of lungs depicted mottling in the form of black, brown or grey in color in 38%, 28%, and 26% of the specimens, respectively. A complete grey, brown, or brownish black color was seen in 2% lungs each. In one lung yellow mottling was seen which could be because of fat deposition. Length of posterior border (19.9cm) was more as compared to anterior border (17.8 cm). Lungs were measured both along lateral and medial surfaces. Along the lateral surface its mean value was 18.52±3.178 cm (Range 12–25 cm) while along medial surface its mean value was 15.11±2.241 cm (Range 9–23 cm). The mean AP width of right lung at center was 11.05±2.864 cm (Range 7–23 cm) and along inferior border was 13.26±2.743 cm (Range 9–20 cm). The mean mediolateral width was found to be 7.536±2.318 cm with range being 4–15.2 cm. Conclusion: Knowledge of normal measurements of lungs and their variations may help cardiothoracic surgeons to avoid undue complications during surgery. Furthermore, it may help radiologist to resolve perplexed radiographic findings.